Trafficking and Sorting of Proteins to the Parasitophorous Vacuolar Membrane of Plasmodium falciparum: PfEXP1 as a Model - Abbasi, Amin; Justus Liebig University Giessen (My University, 2026)
During the asexual blood stage of malaria infection, Plasmodium falciparum develops inside a membrane-bound compartment within the host red blood cell. The membrane surrounding this compartment, the parasitophorous vacuolar membrane (PVM), forms an important interface between parasite and host cell. In addition to exporting soluble effector proteins, the parasite must also direct a specific set of membrane proteins to the PVM. PfEXP1 is a well- established membrane protein of the PVM, but the sequence features that govern its trafficking to this membrane remain unclear. The aim of this thesis was therefore to identify PfEXP1 sequence features that contribute to its targeting to the PVM. To address this question, a panel of plasmid-expressed PfEXP1 variants was generated and analyzed by immunofluorescence microscopy in two parasite developmental stages. In parallel, a biochemical fractionation assay was used to compare whether the different variants behaved mainly as soluble or membrane-associated proteins. Across the construct panel, distal C-terminal truncations generally retained PVM-like localization under the assay conditions used. These variants showed staining patterns consistent with PVM localization and were enriched in the membrane-associated fraction, suggesting that they remained capable of stable membrane association. This indicates that the distal C-terminus is not a dominant determinant of this behavior. In contrast, disruption of the N-terminal region more often resulted in less distinct localization and weaker biochemical evidence for stable membrane association. The transmembrane domain replacement experiments further showed that not all membrane anchors behaved in the same way. Constructs combining the PfEXP1 N-terminal region with a parasite-derived transmembrane segment were more often consistent with PVM-like localization, whereas constructs containing artificial hydrophobic helices did not reproduce clear PVM localization even when flanked by PfEXP1-derived N- and C-terminal regions. These findings argue against a model in which hydrophobicity alone is sufficient for correct targeting. An important limitation of this study was the unexpected predominantly soluble behavior of the exogenous full-length PfEXP1 reference construct, indicating that construct architecture, including tag and linker context, can substantially affect the experimental readout. Taken together, the data support a model in which correct PfEXP1 targeting depends on N-terminal context acting together with an appropriate membrane anchor, whereas the distal C-terminal region appears broadly dispensable in this assay context. More broadly, this work highlights the need for follow-up experiments that directly resolve protein topology, particularly protease- protection assays.
Keywords: Plasmodium falciparum; parasitophorous vacuolar membrane (PVM); PfEXP1; protein trafficking; Malaria; ddc:570